AFF3-DNA methylation interplay in maintaining the mono-allelic expression pattern of XIST in terminally differentiated cells. (7th December 2018) - Zhang, Yue; Wang, Chao; Liu, Xiaoxu; Yang, Qian; Ji, Hongliang; Yang, Mengjun; Xu, Manman; Zhou, Yunyan; Xie, Wei; Luo, Zhuojuan; Lin, Chengqi
Abstract: X chromosome inactivation and genomic imprinting are two classic epigenetic regulatory processes that cause mono-allelic gene expression. In female mammals, mono-allelic expression of the long non-coding RNA gene X-inactive specific transcript ( XIST ) is essential for initiation of X chromosome inactivation upon differentiation. We have previously demonstrated that the central factor of super elongation complex-like 3 (SEC-L3), AFF3, is enriched at gamete differentially methylated regions (DMRs) of the imprinted loci and regulates the imprinted gene expression. Here, we found that AFF3 can also bind to the DMR downstream of the XIST promoter. Knockdown of AFF3 leads to de-repression of the inactive allele of XIST in terminally differentiated cells. In addition, the binding of AFF3 to the XIST DMR relies on DNA methylation and also regulates DNA methylation level at DMR region. However, the KAP1-H3K9 methylation machineries, which regulate the imprinted loci, might not play major roles in maintaining the mono-allelic expression pattern of XIST in these cells. Thus, our results suggest that the differential mechanisms involved in the XIST DMR and gDMR regulation, which both require AFF3 and DNA methylation.